Finger gangrene as initial manifestation of esophageal squamous cell carcinoma: a case report - Chen, Kai; Jiang, Qiongzhi; Zhou, Juju; Yang, Lingya; Zhong, Daquan; Zhai, Tiantian (Frontiers in Oncology, 2025)
Esophageal cancer exhibits a high incidence in the Chaoshan region of south China, an area characterized by distinctive dietary habits prominently featuring the consumption of preserved pickles and hot tea. Common metastatic sites of esophageal cancer include the lungs, liver, brains, and bones, while occurrence in the distal ends of the limbs is exceptionally rare. Here we present a case of a 62-year-old man from China’s Chaoshan region presented with progressive right ring finger pain, swelling, and gangrene. After the amputation of digit, histopathology unexpectedly identified well-differentiated esophageal squamous cell carcinoma (ESCC) with positive margins. A comprehensive retrospective evaluation of medical history identified previously undocumented intermittent dysphagia and mild thoracodorsal pain, postdating the initial presentation of digital symptom by one months. The Esophageal Cancer Multidisciplinary Team confirmed the diagnosis of mid-thoracic ESCC at stage T4bN2M1 according to the AJCC(The American Joint Committee on Cancer, AJCC) 8th edition criteria based on further examinations. Following a multidisciplinary approach encompassing digital amputation, immunochemotherapy, and localized radiotherapy to the primary lesion, the disease achieved partial response according to RECIST(Response Evaluation Criteria in Solid Tumors, RECIST) 1.1 criteria.This case highlights the diagnostic challenges of rare metastatic presentations in ESCC, and the critical importance of recognizing atypical symptoms in high-risk populations. Early multidisciplinary intervention may improve outcomes in rare oligometastatic disease.